Description of two new species of Nannocharax Günther, 1867 (Teleostei: Characiformes: Distichodontidae) from the Cross River, Cameroon - Dunz, Andreas R.; Schliewen, Ulrich K. (Zootaxa, 2009)
Two new species of the African characiform genus Nannocharax Günther, 1867 are described from the Cross River in Cameroon. Nannocharax zebra sp. nov. is distinguished from all other described Nannocharax species except N. schoutedeni Poll, 1939, N. latifasciatus Coenen & Teugels, 1989, N. ansorgii Boulenger, 1911 and N. procatopus Boulenger, 1920 by a shorter distance between the posterior border of the anus and the articulation of the first anal-fin ray (2.2–3.7 vs. 4.2–14.2% of SL). It differs from N. schoutedeni by having 39–43 vs. 36 or 37 lateral line scales, from N. latifasciatus by a deeper caudal peduncle (55.9–63.8% vs. 48.1–50.8% of SL), from N. ansorgii by having 12 or 13 rather than 9 anal-fin rays, and from N. procatopus by having a shorter caudal peduncle (11.3–15.2% vs. 18.0% of SL), and by having 39–43 rather than 36 lateral line scales. Nannocharax usongo sp. nov. is distinguished from all other Nannocharax species mainly in the distance from the border of anus to the articulation of first anal-fin ray (0.9–1.8 vs. 2.2–14.2% of SL) and by its body coloration consisting of 7–11 dark blotches along the lateral line often coalesced to one wide black band, and 7–12 small saddle-blotches along the dorsum.